Soil Testing and Recommentation - Ranjan Kumar Basak; Ranjan Kumar Basak (Ludhiana Kalyani, 2000)
The popularity of the book to the students and their personnels working in soil testing laboratories, Government organisations and Non-Government organizations has greatly encouraged in the book.
Soil Testing Method Plant Testing Kit Soil Fertility Map
Keywords: Soil Testing Method, Plant Testing Kit, Soil Fertility Map